From Abject to Subject: Some Thoughts on Sex Work as a Missing Link in Feminist Understandings of Sexuality - Payne, Kathryn (Atlantis, 2007)
This essay presents some thoughts on the framing of sex work at various stages in the development of Western women's movements. The tenets of victim feminism are critiqued. Observations and impressions from the author's sex work experience support the need for sex worker participation in feminist theorizing about sexuality.